A novel GLI2 mutation responsible for congenital hypopituitarism and polymalformation syndrome. (February 2019) - Martín-Rivada, Álvaro; Rodríguez-Contreras, Francisco Javier; Muñoz-Calvo, Mª. Teresa; Güemes, María; González-Casado, Isabel; del Pozo, Jaime Sánchez; Campos-Barros, Ángel; Argente, Jesús
Abstract: Objective: We report a novel GLI2 frameshift mutation and describe the phenotypic spectrum of mutations within this gene. Patients and methods: A male with congenital hypopituitarism and polymalformation syndrome was clinically, biochemically and neuroradiologically characterized. Genetic analysis for congenital hypopituitarism was performed using a targeted NGS custom gene panel. Results: A heterozygous frameshift mutation, NM_005270.4:c.2125del, p.(Leu709Trpfs*15), was identified in GLI2 exon 12. This mutation has not been previously reported and confirms the diagnosis of Culler-Jones syndrome (MIM #615849 ). Conclusion: GLI2 mutations should be suspected in the presence of congenital hypopitutarism, characteristic facial abnormalities and polydactyly. Highlights: GLI2 mutations should be suspected in the presence of congenital hypopitutarism and polydactyly. A new heterozygous frameshift mutation, NM_005270.4:c.2125del, p.(Leu709Trpfs*15), was identified in GLI2 exon 12. This present case report illustrates the clinical, laboratory, imaging and genotype analysis of a novel loss of function GLI2 mutation. GH deficiency is the most prevalent pituitary hormone deficiency in patients with GLI2 mutations. However, the response to rhGH treatment is inconclusive.